Content Homogenization on Citizen Journalism Platform: Case Study at IDN Times Community - Pratama, Tarida Alif; Aji, Gilang Gusti (The Commercium, 2020)
The existence of the internet accelerates the development of a company, especially the media. The media are competing to be the choice of the reader. The ideology of the media business has changed. The dilemma between social or business interests. Citizen journalism is the solution to survive in the face of intense competition. Citizen journalism that offers citizens freedom to write anything is different now. IDN Times Community limits the freedom of writing with certain themes. As a result, themes that have high commercial value become commodities by IDN Times. Using a critical paradigm with the case study research method, this research found that editorials understood well the contents that were likely to be viral. So the community writer finally follows the virulence of news opportunities that will bring benefits in the form of rewards from IDN Times.